2016
DOI: 10.1177/0890334415625872
|View full text |Cite
|
Sign up to set email alerts
|

A Multifaceted Approach to Revitalizing the Baby-Friendly Hospital Initiative in Croatia

Abstract: The Baby-Friendly Hospital Initiative (BFHI) was launched in Croatia in 1993. By 1998, 15 of 34 maternity facilities were designated "Baby-Friendly." Introduction of hospital bags, violating the International Code of the Marketing of Breastmilk Substitutes, led to a standstill in the BFHI. The aim of this article is to describe the successful reintroduction of the BFHI in Croatia between 2007 and 2015. After hospital bags were abolished in 2007, UNICEF Croatia undertook an assessment of BFHI implementation. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 4 publications
2
19
0
1
Order By: Relevance
“…In the international setting, the BFHI has also been facing numerous challenges for its sustainability and financing [14, 19, 20]. The financing hardships exist both at the government level and internally at maternity hospitals, hampering assessments and the training of employees of Baby-Friendly Hospitals [3].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the international setting, the BFHI has also been facing numerous challenges for its sustainability and financing [14, 19, 20]. The financing hardships exist both at the government level and internally at maternity hospitals, hampering assessments and the training of employees of Baby-Friendly Hospitals [3].…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted in Australia [19], Croatia [20] and some Latin American countries [14] have shown that BFHI’s sustainability depends on several factors. Emphasis is placed on the importance of a robust national breastfeeding policy, with active national and local breastfeeding committees, financial incentive, involvement of hospital managers, articulation between federal and state governments, and the involvement of all sectors of society to support hospitals that wish to be part of this initiative and maintain their title.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, hospital standards fell, and none of the Baby-Friendly designated facilities renewed their status in the subsequent decade. In 2007, the BFHI was revitalized thanks to renewed efforts by UNICEF Croatia and the Ministry of Health (Grgurić, Zakarija-Grković, Pavičić Bošnjak, & Stanojević, 2016), which resulted in all public hospitals becoming Baby-Friendly. In the process, nine maternity facilities were renovated, and two new maternity hospitals were built, including the maternity facility at the University Hospital of Split.…”
Section: Key Messagesmentioning
confidence: 99%
“…The UNICEF programme, the Baby-Friendly Hospital Initiative, was launched in Croatia in 1993 [1]. Today, all Croatia’s maternity wards are baby-friendly.…”
Section: Introductionmentioning
confidence: 99%